The mechanical and morphological properties of HDPE composites filled with SiO2, ZnO, Mg(OH)2 and CaCO3 nano powder [Proprietǎţile mecanice şi morfologice ale compozitelor pe bazǎ de hdpe ranforsate cu nanopulberi de SiO2, ZnO, Mg(OH)2 şi CaCO3] - (:unkn) unknown (My University, 2013)
Thermoplastic resin-mineral filler composites have been widely used in molded products due to effective cost reduction. Generally, the addition of mineral fillers will have an embrittling effect on polymers although the rigidity of the polymers can be increased. Much effort has been devoted to improving the properties of polymers by the addition of inorganic fillers, such as SiO2, ZnO, CaCO3 and Mg(OH)2. In this study, mechanical properties of the high density polyethylene (HDPE) composites filled with silicon dioxide (SiO2), zinc oxide (ZnO) magnesium hydroxide [Mg(OH)2] and calcium carbonate (CaCO3) were investigated. The structure and properties of the composites are characterized using a scanning electron microscopy (SEM) and Energy dispersive X-ray spectroscopy (EDS). Furthermore, HDPE composites were subjected to examinations to obtain their tensile strengths, yield strengths, elasticity modulus, % elongation, Izod impact strength, hardness and melt flow index (MFI).
Keywords: Calcium carbonate; Magnesium hydroxide; Silicon dioxide; Zinc oxide